2021
DOI: 10.1051/parasite/2021060
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anthelmintic activity of an aqueous extract of Glycyrrhiza glabra and of glycyrrhetinic acid against gastrointestinal nematodes of small ruminants

Abstract: This study evaluated the in vitro anthelmintic activity of a liquorice (Glycyrrhiza glabra) root aqueous extract and of glycyrrhetinic acid at 30, 10, 5, 1, and 0.5 mg/mL against sheep gastrointestinal nematodes (GINs), using the egg hatch test (EHT), the larval development test (LDT), and the larval migration inhibition test (LMIT). The compounds were applied on a mixture of GIN eggs and larvae, mainly Trichostrongylus spp. and Teladorsagia/Ostertagia spp. Cytotoxicity assays were also performed. In the EHT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Indeed, the study focused on the evaluation of the anthelmintic activity of the extracts of these two plants through in vitro biological tests on the eggs and the adult worms of H. contortus which constitute two stages of the development cycle of this parasite. The methods of inhibition of egg hatching and adult worm motility were used for these in vitro tests according to several previous works [6,14,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the study focused on the evaluation of the anthelmintic activity of the extracts of these two plants through in vitro biological tests on the eggs and the adult worms of H. contortus which constitute two stages of the development cycle of this parasite. The methods of inhibition of egg hatching and adult worm motility were used for these in vitro tests according to several previous works [6,14,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…GA also demonstrated anti-parasitic activity [38][39][40]. GA suppressed inflammation in Leishmania donovani infection by inhibiting COX-2-mediated prostaglandin E2 (PGE2) release in L. donovani-infected macrophages [38].…”
Section: Antiviral and Anti-parasitic Activitymentioning
confidence: 99%
“…This evaluation revealed that GA kills the parasite by affecting the sterol biosynthetic pathway, especially by inhibiting the L. donovani HMGR (3-hydroxy-3-methylglutaryl coenzyme A reductase) and altering ergosterol levels [41]. The in vitro anthelmintic activity of GA against gastrointestinal nematodes of small ruminants was investigated by Maestrini et al (2021). In this study, GA was found to be highly active when used in the egg hatch test (EHT), larval development test (LDT), and larval migration inhibition test (LMIT) [40].…”
Section: Antiviral and Anti-parasitic Activitymentioning
confidence: 99%
See 2 more Smart Citations